Financing Nuclear Power Plants - IAEA (International Atomic Energy Agency, 2021)
This publication, which presents the outcome of an IAEA coordinated research project on financing nuclear power plants, contributes to the understanding of the specific challenges posed. Based on the experience of those Member States recently involved in financing nuclear projects, the publication identifies the lessons which could be drawn relating to the sources of financing, the nature of the financing process and the barriers to financing nuclear projects.